Shear and Tensile Strength in a Complex (Zirconia Crown, Resin Core, FRC Post) Adhesive with Resin Cement - عيسى, نزيه; معلا, زينة (Latakia University Journal -Medical Sciences Series, 2020)
The resistance of endodontically treated teeth to fracture is directly related to the strength of the remaining tooth structure, where the main risk when restoring these teeth is the loss and weakening of coronally structures, which leads to an increased probability of fracturing the tooth under different loading forces. In recent years, interest in All ceramic restorations has increased due to the high aesthetic, including the zirconia crowns, and this necessitated the replacement of metal posts with another that secures these aesthetic requirements more efficiently, And allows the preservation and support of future restoration. so the use of the fiber-reinforced posts system was one of these options. The choice of cementing cement is a key factor in ensuring crown stability, thus preventing premature failure of the complex (post-core -crown). This laboratory study was carried out at the Faculty of Dentistry at Tishreen University and the Center for Industrial Testing and Research in Damascus. It aims to evaluate the durability of zirconia crowns over the teeth supported by the glass fiber reinforced resin post in the (crown-post-core-root) compound, and the amount of force causing the failure resulting from their application, when using the complex: Composite, crown of zirconia adhesive with resin cement). The 12 samples were collected from the one-root canal premolars, and divided equally for two tests: shear test: performed on 6 premolars, and tensile test: performed on 6 premolars. Mechanical tests of the shear and tensile specimens were performed after the endodontically treatment of these teeth, the placing of resin posts and the cores of the composites, and crowned with crowns of zirconia adhesive with resin cement. The strength of the cement bonds with the fiber reinforced resin posts was evaluated with a core of composite, and zirconia crowns, where it was found that the highest shear bonding strength was (571.167) Newton, which is higher than the normal chewing forces of an average of (350) Newton. The most important conclusions of the study That the crown of zirconia showed good stability when adhesived to resin cement, and the stability of the glass fiber reinforced resin post adhesived with resin cement, when applying shear and tensile forces within the limits of the natural chewing forces.